A modified Monti procedure using a Meckel's diverticulum - Nicola Cullen; Abdulrahman Alshafei; Feargal Quinn (Elsevier, 2020)
The Mitrofanoff procedure has enhanced practical management of urinary incontinence over the past 20 years by means of an abdominal stoma catheterisation for patients suffering from neuropathic bladder. This procedure has been modified when there is no viable appendix to enable similar tubularisation and conduit formation from parts of the gastrointestinal tract, also known as the Monti technique. While ileum is more consistently used in a Monti procedure, in this particular case a Meckel's Diverticulum (MD) lent for an alternative option. Herein, this case report allows us to demonstrate the use of a MD as a viable option if and when the opportunity allows, in the absence of appendicular tissue.